2016
DOI: 10.1016/j.jfoodeng.2015.10.019
|View full text |Cite
|
Sign up to set email alerts
|

In silico modelling of mass transfer & absorption in the human gut

Abstract: An in silico model has been developed to investigate the digestion and absorption of starch and glucose in the small intestine. The main question we are aiming to address is the relative effect of gastric empting time and luminal viscosity on the rate of glucose absorption. The results indicate that all factors have a significant effect on the amount of glucose absorbed. For low luminal viscosities (e.g. lower than 0.1 Pas) the rate of absorption is controlled by the gastric emptying time. For viscosities high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 63 publications
0
36
0
Order By: Relevance
“…Much of the existing work is based on continuum approaches, see e.g. [12,13] and the reviews in Refs. [11,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Much of the existing work is based on continuum approaches, see e.g. [12,13] and the reviews in Refs. [11,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Numerical modelling of the digestive system has been carried out from both a pharmacokinetic ( Di Muria et al, 2010 , Peng and Cheung, 2009 , Stoll et al, 2000 , Yu et al, 1996 ), and a food science perspective ( Bastianelli et al, 1996 , Dalla Man et al, 2006 , Logan et al, 2002 , Moxon et al, 2016 , Penry and Jumars, 1986 , Penry and Jumars, 1987 , Taghipoor et al, 2012 , Taghipoor et al, 2014 ). The general approach is to break the digestive system into compartments which can be described as ideal reactors.…”
Section: Introductionmentioning
confidence: 99%
“…This work will build upon a model previously developed in Moxon et al (2016) . The aim is to demonstrate the viscosity of a liquid meal affects the mass transfer of nutrients within the intestine, and will influence the gastric emptying rate via a feedback mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Hiimae et al (Hiiemae et al 1996) showed that the average particle size scales inversely with food hardness, while the number of bites increases. Moreover, large and hard solid particles demonstrate low gastric emptying rates, as opposed to small and soft in which the rates are profoundly higher (Kong and Singh 2008;Drechsler and Ferrua 2016); the same trend corresponds between high and low viscosity fluids (Moxon, Gouseti, and Bakalis 2016). Controlling the gastric emptying rate receives considerable attention, because it associates with metabolic effects and the management of obesity (Cohen et al 2003;CardosoJúnior et al 2007), both in humans and pets (German et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It is also strongly related to diabetes and stomach disorders such as dyspepsia (Rayner et al 2001). Summarising, there is an increasing need in models of food breakdown not only to address a healthy oral processing but also to aid in a controlled gastrointestinal digestion (Moxon, Gouseti, and Bakalis 2016;Taghipoor et al 2012;Norton, Moore, and Fryer 2007).…”
Section: Introductionmentioning
confidence: 99%